Husnudzan and Anxiety in Students Dealing with National Examination - Shabrina, Nur Baity Ulya; Rachmawati, Mira Aliza (Universitas Muhammadiyah Surakarta, 2019)
National exams as an evaluation stage of learning often make students feel anxious. anxiety arises because of perceptions about the inability to deal with themselves and have an impact on the disruption of thinking patterns and physical responses and behaviors because of the possibility of the performance displayed by students is not well received while doing the test. Perceiving positive things to God is one form of worship dimensions manifested in Husnudzan’s attitude. Husnudzan means to be prejudiced towards God in dealing with all problems that make a person feel peaceful and secure. Negative perceptions of students in facing exams that cause anxiety can be rectified with positive thinking patterns. This will lead to both positive perceptions and behavior based on Husnudzan’s attitude. This study uses a literature study method that explains how Husnudzan can influence student anxiety in facing a national exam.